Sfide bioetiche in Neurogenomica da una prospettiva interreligiosa e multiculturale - Tham, L.C., Joseph (Studia Bioethica, 2017)
The 5th International Bioethics, Multiculturalism and Religion Workshop and Conference organized by the UNESCO Chair in Bioethics and Human Rights was held at the MD Anderson Cancer Center, Houston, USA from November 14 - 16, 2016. The theme discussed was entitled, “Bioethical Challenges in Neurogenomics from an Interreligious and Multicultural Perspective.” On this occasion, 30 bioethicists and religious scholars from six major religious traditions actively participated and debated about the implications of these new technologies.Il 5° Workshop e Conferenza Internazionale di Bioetica, Multiculturalità e Religione, organizzato dalla Cattedra UNESCO di Bioetica e Diritti Umani, si è tenuto dal 14 al 16 novembre 2016 presso il MD Anderson Cancer Center di Houston, USA. Il tema discusso è stato: "Sfide bioetiche in Neurogenomica da una prospettiva interreligiosa e multiculturale". In questa occasione, 30 bioeticisti e studiosi religiosi di sei grandi tradizioni religiose hanno partecipato attivamente e hanno discusso le implicazioni di queste nuove tecnologie.